LACTOPEROXIDASE IMMOBILIZED ONTO VARIOUS BEADS FOR PRODUCING NATURAL PRESERVATIVES SOLUTION - Ahmad Ni'matullah Al-Baarri; M Ogawa; T Visalsok; S Hayakawa (Indonesian Food Technologists, 2012)
The natural preservative agent of hypothiocyanite (OSCN–) has been succeded to determine using immobilized LPO onto various types of beads or matrixes: SP Sepharose Fast Flow (SP-FF), SP Sepharose Big Beads (SP-BB), CNBr activated SP Sepharose (SP-CNBR). Lactoperoxidase (LPO) was obtained from bovine milk. The immobilization method was performed using ion exhange method and adsorption. Immobilized LPO onto matrixes has been stored for 7 days at 4˚C and 10˚C. Data of the production of OSCN– were collected before and after immobilized LPO storage. Data shows no remarkable effect of the production of OSCN– using immobilized LPO stored at 4˚C, however, the remarkable reduction has been detected in the production of OSCN– using immobilized LPO that was stored at 10˚C. As a conclusion, the 7 days storage does not change the capability of immobilized LPO for producing OSCN if the immobilized LPO was stored at 4˚C.